KETIDAKSETARAAN GENDER DALAM AKSES PENDIDIKAN FORMAL DI GAMPONG LHOK GUCI KECAMATAN PANTE CEUREUMEN - Cut Intan Fonna; Irsya Diah; Riska Utama; Sopar Sinambela (Sosietas: Jurnal Pendidikan Sosiologi, 2024)
Gander inequality in education in the case study of Gampong Lhok Guci caused very significant social changes for the local community. Based on this, the main aim of this research is to reveal the root of the problem of gender inequality in education in Gampong Lhok Guci. The method used in this research is a qualitative method, namely to understand symptoms such as behavior, violations, attitudes, actions and points of view, clear analysis is needed. Data collection methods used in this research include interviews, documentation and observation. This research also uses secondary data obtained through journals, reports, books and the internet. Meanwhile, this research also uses primary data obtained from informants during field interviews. In this case study, it is analyzed using the social construction theory put forward by Peter L. Berger and Thomas Luckman. These experts argue that the construction of social reality is a process of meaning carried out by each individual regarding the environment and aspects outside themselves. Social change and increased awareness of the importance of education for all genders are needed to create greater educational equality.